The Influence of Knowledge Management and Islamic Leadership on Organizational Decision Making for Middle School Muslim Youth Development - Panduwiyasa, Haryasena (Universitas Muhammadiyah Magelang, 2022)
Islamic youth development and da'wah organizations frequently face constraints in the decision-making process, both those carried out in the secondary level education sector. This is caused by the low effectiveness of the knowledge sharing process carried out between members, the lack of direction and support from the leadership or strategy, and the low quality of information management are the main factors for failure in the knowledge management process in a work program as well as the overall activities of Islamic youth da'wah organizations. The lack of facilities in managing the historical activity track record has hampered the decision-making process in organizational knowledge. Misunderstandings and lack of knowledge also lead to the loss of ghirah (da'wah motivation) and ukhuwah (familial relationships) in Islamic youth da'wah organizations in the education sector. This study aims to prove how knowledge management activities carried out in a structured manner by da'wah organizations, which aim to guide Islamic youth in high school (SMA/K) and junior high school (SMP) can transform information into valuable assets in managing Islamic da'wah operations and decision making that need to be carried out by the organization in the long term based on the determining factors, including managing aspects of knowledge management and Islamic-based leadership character. The methods and data processing carried out in this study used a quantitative-confirmatory approach and used multiple linear regression analysis, through the distribution of questionnaires to members of the XYZ high school Muslim youth development organization in Bandung Regency. The results and conclusions of this study prove that there is a significant positive influence from the application of knowledge management carried out in a structured manner up to 47.1% and Islamic-based leadership abilities up to 41.9%, on the decision-making process of Muslim youth development organizations in secondary schools, as well as Islamic-based education in general.